Novel CaMKII-δ Inhibitor Hesperadin Exerts Dual Functions to Ameliorate Cardiac Ischemia/Reperfusion Injury and Inhibit Tumor Growth. Issue 15 (24th March 2022) - Zhang, Junxia; Liang, Ruqi; Wang, Kai; Zhang, Wenjia; Zhang, Mao; Jin, Li; Xie, Peng; Zheng, Wen; Shang, Haibao; Hu, Qingmei; Li, Jiayi; Chen, Gengjia; et al.
Abstract : Background: Cardiac ischemia/reperfusion (I/R) injury has emerged as an important therapeutic target for ischemic heart disease, the leading cause of morbidity and mortality worldwide. At present, there is no effective therapy for reducing cardiac I/R injury. CaMKII (Ca 2+ /calmodulin-dependent kinase II) plays a pivotal role in the pathogenesis of severe heart conditions, including I/R injury. Pharmacological inhibition of CaMKII is an important strategy in the protection against myocardial damage and cardiac diseases. To date, there is no drug targeting CaMKII for the clinical therapy of heart disease. Furthermore, at present, there is no selective inhibitor of CaMKII-δ, the major CaMKII isoform in the heart. Methods: A small-molecule kinase inhibitor library and a high-throughput screening system for the kinase activity assay of CaMKII-δ9 (the most abundant CaMKII-δ splice variant in human heart) were used to screen for CaMKII-δ inhibitors. Using cultured neonatal rat ventricular myocytes, human embryonic stem cell–derived cardiomyocytes, and in vivo mouse models, in conjunction with myocardial injury induced by I/R (or hypoxia/reoxygenation) and CaMKII-δ9 overexpression, we sought to investigate the protection of hesperadin against cardiomyocyte death and cardiac diseases. BALB/c nude mice with xenografted tumors of human cancer cells were used to evaluate the in vivo antitumor effect of hesperadin. Results: Based on the small-molecule kinase inhibitor library and screening system, we found that hesperadin, an Aurora B kinase inhibitor with antitumor activity in vitro, directly bound to CaMKII-δ and specifically blocked its activation in an ATP-competitive manner. Hesperadin functionally ameliorated both I/R- and overexpressed CaMKII-δ9–induced cardiomyocyte death, myocardial damage, and heart failure in both rodents and human embryonic stem cell–derived cardiomyocytes. In addition, in an in vivo BALB/c nude mouse model with xenografted tumors of human cancer cells, hesperadin delayed tumor growth without inducing cardiomyocyte death or cardiac injury. Conclusions: Here, we identified hesperadin as a specific small-molecule inhibitor of CaMKII-δ with dual functions of cardioprotective and antitumor effects. These findings not only suggest that hesperadin is a promising leading compound for clinical therapy of cardiac I/R injury and heart failure, but also provide a strategy for the joint therapy of cancer and cardiovascular disease caused by anticancer treatment.